2009
DOI: 10.2147/idr.s4083
|View full text |Cite
|
Sign up to set email alerts
|

Doripenem in hospital infections: a focus on nosocomial pneumonia, complicated intra-abdominal infections, and complicated urinary tract infections

Abstract: Doripenem is the latest carbapenem on the market to date. Although not an antibiotic in a new class, it offers a glimmer of hope in combating serious infections secondary to multidrug-resistant Gram-negative bacteria when we have not seen a new class of antibacterial, particularly for Gram-negative bacteria, for more than 10 years. In vitro, doripenem exhibits a broad spectrum of activity against Gram-positive and Gram-negative bacteria, including extended-spectrum β-lactamase (ESBL) and Amp-C β-lactamase prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Additionally, the clinical success rate was 89.4% and ranged from 70.3% to 100.0%. Our findings are in line with the findings of a review [16] of several clinical trials conducted by Lo et al and a recent meta-analysis [17], both of which reported that doripenem was not inferior to the comparators, such as meropenem, imipenem, piperacillin/tazobactam, or levofloxacin, in its efficacy and safety profile in patients with a wide range of serious hospital-acquired infections. Thus, these results suggest that doripenem may serve as an effective treatment option in the armamentarium of antibiotics available to treat HCAIs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the clinical success rate was 89.4% and ranged from 70.3% to 100.0%. Our findings are in line with the findings of a review [16] of several clinical trials conducted by Lo et al and a recent meta-analysis [17], both of which reported that doripenem was not inferior to the comparators, such as meropenem, imipenem, piperacillin/tazobactam, or levofloxacin, in its efficacy and safety profile in patients with a wide range of serious hospital-acquired infections. Thus, these results suggest that doripenem may serve as an effective treatment option in the armamentarium of antibiotics available to treat HCAIs.…”
Section: Discussionsupporting
confidence: 92%
“…The microbiological response to doripenem observed in the present work was similar to that reported in the study conducted by Vazquez et al in which favorable microbiological responses were achieved in 71.4% of the 35 microbiologically evaluable patients receiving imipenem treatment for complicated urinary tract infection in a hospitalized adult population [19]. Therefore, both our findings and those of previous reports [16,18] suggest that doripenem may be as useful as other carbapenems for the treatment of hospital-associated urinary tract infections.…”
Section: Discussionsupporting
confidence: 92%
“…This study suggests that doripenem use may be beneficial both economically and clinically to patients. 15 The current meta-analysis suggests that there is no significant difference between doripenem and comparator drugs on treatment efficacy and safety, but doripenem remains a valuable alternative as it has several advantages. First, a total daily dose of 1.5 g of doripenem is equivalent to 3 g of meropenem or 2-3 g of imipenem in terms of clinical and microbiological cure rates.…”
Section: Discussionmentioning
confidence: 97%
“…Doripenem-treated patients compared with imipenem-treated patients showed reductions in median LOS (24 vs. 37 days), median ICU LOS (15 vs. 17 days), and median time on mechanical ventilation (7 vs. 13 days). Lo and colleagues 132 confirm these findings, suggesting the broad spectrum of activity and efficacy of doripenem contribute to relative cost benefits (including significantly reduced LOS and time needed on mechanical ventilation) that may make it the drug of choice in the treatment of serious nosocomial infections. Further studies with larger samples are warranted to test the hypothesis that doripenem improves medical resource utilization in VAP patients with P. aeruginosa infection.…”
Section: Health Economic Perspectivesmentioning
confidence: 84%